KARAKTERISTIK AIR ASAM TAMBANG DI LINGKUNGAN TAMBANG PIT 1 BANGKO BARAT, TANJUNG ENIM SUMATERA SELATAN SEBUAH STUDI KASUS ASAM TAMBANG - Hidir Tresnadi (Jurnal Teknologi Lingkungan, 2008)
In Coal Mine Pit 1, Bangko Barat, Tanjung Enim, South Sumatera mine activity lowered the water pH in the effluent water of the mine. So the Mine Environmet Managemet of PTBA try to raise the pH to meet Kep Men Neg LH No 113 Tahun 2003. This study attempt to characterize the performance of the water treatment,which managed by acid-mine dranage management of the PTBA. Some water samples was taken in the study area, such as the passive treatment in Pit 1 Bangko Barat, rainwater pond near by, lake, mine sump, settling pond, the water treatment of acid mine drainage in the coal stockpile in Bangko Barat, the mine sump of Air Laya Mine and Air Laya Channel. The result of the study showed that in the coal stockpile the pH is around 5, closed to the pH di rainwater pond and Air Laya putih Channel (around 6), output of water treatment in Tambang Air Laya. Meanwhile thepH in the passive treatment, settling pond, mine sump Banko Barat and in Air laya Mine drainage system is 2 - 3. The source of Acid Mine Rocks is coal seam rock interval and overburden of the coal. Meanwhile the performance of water treatment in the lake, Air Laya Putih channel and coal stockpile better than in the passivetreatment, settling pond, mine sump of Air Laya MIne and pit 1 Banko barat. So PTBA Environment division should improve the process capacity of water treatment in the pit of Bangko Barat.